Comparação de diferentes métodos de síntese após lobectomia pulmonar parcial em cães. - Paloma Helena Sanches da Silva (2022)
In the search for a model of aerostasis that can ensure greater safety regarding the pneumostatic property after lung surgeries in dogs, the objective of this study was to compare the hermeticism promoted by different synthesis methods after partial lobectomy in the right caudal lung lobe of dogs using 30 lung models in cadaveric respiratory blocks obtained immediately or within 12 hours after death. The 30 anatomical pieces collected after necropsy of young dogs were divided equally into five groups according to the synthesis method to be analyzed, resulting in six experimental unit seach. Group 1 (G1) consisted of lung lobes that received, as synthesis, the cobbler pattern associated with simple continuous suture; group 2 (G2), suture in a continuous overlapping pattern associated with simple continuous suture; group 3 (G3), suture in Reverdin pattern; group 4 (G4), mechanical suturing using metallic staples from the thoracoabdominal linear surgical stapler; and group 5 (G5), synthesis with tissue adhesive based on a cyanoacrylate comonomer. After using the surgical technique in lung parenchyma and with the trachea of the respiratory block intubated, the lungs were submerged in water followed by insufflation with oxygen at positive ventilatory pressures. at physiological (20 cmH2O) and supraphysiological levels to perform the aerostasis test and record the pressures in which air escape occurred then. All groups were statistically analyzed and there was no difference between groups when submitted to levels of physiological ventilatory pressures (up to 20 cmH2O), demonstrating adequate aerostasis. However, when evaluating such methods at ventilation pressure levels above 20 cmH2O, a superiority of the synthesis promoted by the tissue adhesive containing cyanoacrylate comonomer was observed. in relation to the groups that received sutures in the Reverdin pattern and with staples. It is concluded, therefore, that manual sutures in the cobbler pattern with simple continuous, continuous overllaping with simple continuous and Reverdin, as well as mechanical sutures and synthetic sealant are able to promote aerostasis after partial lung resection in dogs, when at physiological ventilatory pressures, and that the synthesis with the synthetic surgical glue proved to be superior to the synthesis methods with Reverdin pattern and metallic staples, promoting safer aerostasis after partial lung lobectomy in dogs by resisting supraphysiological levels of ventilatory pressure.